FOSTERING DIGITAL LITERACY THROUGH GLAM COLLABORATION: THE STRATEGIC ROLE OF LIBRARIES IN EDUCATIONAL TRANSFORMATION - Nawwaf Faruq Adina Putra; Imam Yuadi; Hendro Margono (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Digital transformation has fundamentally changed the ways information is accessed, evaluated, and utilized, making digital literacy an essential competence in contemporary education. Within this context, Galleries, Libraries, Archives, and Museums (GLAM) hold significant potential as providers of cultural and knowledge resources that support learning in the digital era. This article examines the strategic role of libraries in fostering digital literacy through GLAM collaboration as part of educational transformation. The study employs a Systematic Literature Review (SLR) method by analyzing 17 peer-reviewed articles published between 2013 and 2024, retrieved from Google Scholar, Scopus, ScienceDirect, DOAJ, and JSTOR. The findings indicate that libraries are well positioned to act as central coordinators of GLAM collaboration due to their established digital infrastructure, expertise in information organization, and metadata management capabilities. Five key themes emerge from the analysis: the urgency of GLAM integration in digital education, libraries as strategic connectors among GLAM institutions, the contribution of GLAM to digital literacy development, collaborative learning models supported by GLAM, and socio-technical challenges in implementation. Overall, GLAM collaboration led by libraries enhances critical thinking, information evaluation, and contextual understanding through access to authentic and multimodal resources. This study highlights the transformative leadership role of libraries within the GLAM ecosystem in higher education.